Experimental endogenous endophthalmitis caused by Haemophilus influenzae type b. - Myerowitz, R L (1976)
Experimental endogenous endophthalmitis was produced in infant rats by either intranasal or intraperitoneal inoculation with Haemophilus influenzae type b and 5 days of age. The ocular disease occurred in about 50% of bacteremic animals who survived to age 12 days and probably represents metastatic bacterial infection secondary to hematogenous seeding. The lesion was a highly destructive suppurative endophthalmitis that ultimately progressed to panophthalmitis and was followed by organization of the exudate and phthisis bulbi.